The relationship between unwarranted variation in optometric referrals and time since qualification. (2nd September 2018) - Parkins, David J; Benwell, Martin J; Edgar, David F; Evans, Bruce J W
Abstract: Purpose: To investigate variation in optometric referral decision‐making and the influence of experience and continuing education and training (CET). Methods: To gain insight into unwarranted variation in referral activity in the United Kingdom (UK): (1) triage data were audited to investigate source of referral, provisional diagnosis, and outcome; (2) an online system was developed to present two sets of 10 vignettes, designed to avoid prompting answers. Participating optometrists completed 10 pre‐CET vignettes, recording their tests and management decisions. The main group of participants chose whatever CET they wished over a 6‐month period and then completed another 10 post‐CET vignettes. A second group of newly‐qualified optometrists completed the vignettes before and after a CET course intervention, followed by a third group of pre‐registered optometrists with an intervention of 6‐months experience of their pre‐registration year. Results: The audit identified 1951 optometric referrals and 158 optometrists (211 referrals were from general medical practitioners), with 122 of the 158 optometrists making fewer than ten referrals. Two newly‐qualified optometrists generated 12.5% of the total referrals in the audit ( N = 2162). Many suspect glaucoma referrals were based on a single suspect measurement resulting in a high discharge rate after community review, as did referrals for certain fundus‐related appearances for which no treatment was indicated. The intervention of gaining CET points appeared to have no significant impact ( p = 0.37) on referral decision‐making, although this part of the study was underpowered. Self‐selection bias was confirmed in the main group. When the main group and newly‐qualified practitioners were compared, the number of referrals was negatively associated with time since qualification ( p = 0.005). When all 20 referral decisions were compared, all optometrists referring more than 10 vignette patients came from a group of newly‐qualified practitioners up to 2 years post‐qualification. Pre‐registered optometrists generally referred more appropriately than newly‐qualified. Upon qualification, there was a significant increase in the number of sight tests undertaken per day ( p = <0.0005). Conclusions: Gaining CET points alone is unlikely to significantly improve referral decision‐making. Mentoring and targeted CET for the newly‐qualified up to 2 years post‐qualification should be considered. Ophthalmology replies to the referring newly‐qualified optometrist are vital for moderating future referrals and developing clinical confidence.